Randomized Controlled Clinical Trial of Two Surgical Techniques for Primary Pterygium in Jungle Patients: Cauterization versus Suturing. - Armas Herrera, Gioconda (2024)
Objective: To compare two surgical techniques for excising pterygium, by evaluating postoperative symptoms and the incidence of recurrence. Methods: Randomized controlled clinical trial with two parallel groups and a single-blind design involving eighty patients with primary pterygium from the Ophthalmological Clinic of the Jungle. The first group considered the autograft fixation technique with bipolar cautery (n=40), and the second group considered the conventional autograft fixation technique with sutures (n=40). Symptoms were assessed at 72 hours postoperatively, and recurrence was evaluated at six months. Results: At 72 hours post-surgery, 6% of patients operated with the electrocautery technique exhibited symptoms, compared to 41% of those operated with sutures (p < 0.05). Recurrence was observed in 1 case in the electrocautery group and 4 in the suture group (2.5% vs. 10%, p < 0.05). Conclusions: The cautery technique demonstrated a more favorable recovery, with fewer symptoms and recurrence compared to the conventional technique. These findings suggest that the cautery technique may be more effective and better tolerated in patients in this study.